Intermittent hypoxia impairs glucose homeostasis in C57BL6/J mice: partial improvement with cessation of the exposure - Polak, Jan; Shimoda, Larissa A; Drager, Luciano F; Undem, Clark; McHugh, Holly; Polotsky, Vsevolod Y; Punjabi, Naresh M (Sleep, 2013)
OBJECTIVES: Obstructive sleep apnea is associated with insulin resistance, glucose intolerance, and type 2 diabetes mellitus. Although several studies have suggested that intermittent hypoxia in obstructive sleep apnea may induce abnormalities in glucose homeostasis, it remains to be determined whether these abnormalities improve after discontinuation of the exposure. The objective of this study was to delineate the effects of intermittent hypoxia on glucose homeostasis, beta cell function, and liver glucose metabolism and to investigate whether the impairments improve after the hypoxic exposure is discontinued. INTERVENTIONS: C57BL6/J mice were exposed to 14 days of intermittent hypoxia, 14 days of intermittent air, or 7 days of intermittent hypoxia followed by 7 days of intermittent air (recovery paradigm). Glucose and insulin tolerance tests were performed to estimate whole-body insulin sensitivity and calculate measures of beta cell function. Oxidative stress in pancreatic tissue and glucose output from isolated hepatocytes were also assessed. RESULTS: Intermittent hypoxia increased fasting glucose levels and worsened glucose tolerance by 67% and 27%, respectively. Furthermore, intermittent hypoxia exposure was associated with impairments in insulin sensitivity and beta cell function, an increase in liver glycogen, higher hepatocyte glucose output, and an increase in oxidative stress in the pancreas. While fasting glucose levels and hepatic glucose output normalized after discontinuation of the hypoxic exposure, glucose intolerance, insulin resistance, and impairments in beta cell function persisted. CONCLUSIONS: Intermittent hypoxia induces insulin resistance, impairs beta cell function, enhances hepatocyte glucose output, and increases oxidative stress in the pancreas. Cessation of the hypoxic exposure does not fully reverse the observed changes in glucose metabolism.
Keywords: modely nemocí na zvířatech; Animals; oxidační stres; Glucose; myši inbrední C57BL; Oxidative Stress; Hypoxia; Insulin-Secreting Cells; glukózový toleranční test; Disease Models, Animal; hypoxie; glukosa; zvířata; homeostáza; obstrukční spánková apnoe; myši; Blood Glucose; inzulinová rezistence; Insulin Resistance; Glucose Tolerance Test; Sleep Apnea, Obstructive; beta-buňky; krevní glukóza; Mice; Mice, Inbred C57BL; Homeostasis